2017
DOI: 10.1080/10717544.2017.1319433
|View full text |Cite
|
Sign up to set email alerts
|

Effective intraperitoneal gene transfection system using nanobubbles and ultrasound irradiation

Abstract: In this study, we demonstrate the low toxicity and highly efficient and spatially improved transfection of plasmid DNA (pDNA) with liposomal nanobubbles (bubble liposomes [BLs]) using ultrasound (US) irradiation in mice. Naked pDNA with BLs was intraperitoneally injected, followed by US irradiation. The injection volume, the duration of US irradiation, and the dose of BLs were optimized. Both BLs and US irradiation were essential to achieve high transgene expression from naked pDNA. We observed transgene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…Additional examination by injection of two plasmids, encoding ZsGreen and tdTomato fluorescent proteins revealed that ZsGreen can be imaged deeper into the tissue (1500 µm vs 1200 µm) with the latter being also less photostable, when placed in CUBIC reagent 2. These results are corroborated by a further study of the same group led by Nishimura et al . who also performed SeeDB and Clear T2 ‐based liver clearing post gene transfection using bubble liposomes with ultrasound irradiation, achieving only modest transparency allowing for ≈100 µm in depth examination of the peritoneal tissues.…”
Section: Application Of Toc For Particular Peripheral Organssupporting
confidence: 58%
“…Additional examination by injection of two plasmids, encoding ZsGreen and tdTomato fluorescent proteins revealed that ZsGreen can be imaged deeper into the tissue (1500 µm vs 1200 µm) with the latter being also less photostable, when placed in CUBIC reagent 2. These results are corroborated by a further study of the same group led by Nishimura et al . who also performed SeeDB and Clear T2 ‐based liver clearing post gene transfection using bubble liposomes with ultrasound irradiation, achieving only modest transparency allowing for ≈100 µm in depth examination of the peritoneal tissues.…”
Section: Application Of Toc For Particular Peripheral Organssupporting
confidence: 58%
“…L-Ascorbic acid was purchased from Wako Pure Chemical Industries, Ltd. (Osaka, Japan) and dissolved in water at 10 mg/mL. BLs composed of 1,2-Distearoyl-sn-glycero-3-phosphocholine (DSPC) (Avanti Polar Lipids, Inc., Alabaster, Alabama, USA) and 1,2-distearoyl-sn-glycero-3-phosphatidylethanolaminemethoxy-polyethyleneglycol (DSPE-PEG (2k)-OMe) (NOF Corporation, Tokyo, Japan) (94:6 (m/m)) were prepared according to previous reports at 1 mg/mL in terms of their lipids [16,17,20,21]. To encapsulate the perfluoropropane gas into BLs, vials were vortexed in a sonicated bath (BRANSONIC B1200, Emerson Electric Co., St. Louis, MO, USA).…”
Section: Preparation Of Drugs and Blsmentioning
confidence: 99%
“…Our group has been developing DDS for liver [13], spleen [14], solid tumours [15,16], and peritoneal tissues [17] using ultrasound-responsive bubble formulations.…”
Section: Introductionmentioning
confidence: 99%
“…We developed 3-dimensional multicolor deep imaging, applied with a combination of the tissue clearing methods, with observation by confocal laser microscopy. 16,18,19) This 3-dimensional multicolor deep imaging was then applied to analyze the spatial distribution of transgene expression in the suctioned liver. We evaluated the selectivity and depth of transgene expression using CUBIC reagents 20) that have high sensitivity for transgene expression.…”
mentioning
confidence: 99%